Flies from meat processing facilities are carriers of multidrug-resistant Escherichia coli and diverse Staphylococcaceae species - Matheus Zorzal Bernardes Rangel; Gustavo Guimarães Fernandes Viana; Ana Julia Camuzzi Ferrari Storck; Carolina Magri Ferraz; Sarah Bernardes Simões; Valéria Modolo Peterle; Natalia Pereira; Pamella Almeida Freire Casemiro; Alessandra Figueiredo de Castro Nassar; Vanessa Castro; Bruna Maria Salotti-Souza; Juliano Gonçalves Pereira; et al. (Brazilian Journal of Microbiology, 2026)
Flies are important vectors of antimicrobial resistance (AMR) in food production, but their role in meat processing environments remains poorly characterized. This study isolated Enterobacteriaceae and Staphylococcaceae (including Mammaliicoccus sciuri ) from flies collected in bovine and swine slaughterhouses and meat processing industries. Phenotypic AMR was assessed, and the presence of selected antimicrobial resistance and virulence genes ( mecA , sea , see , sec , stx1 , stx2 , and eae ) was verified. Out of 60 flies collected, a total of 34 isolates were identified using MALDI-TOF with 13 different bacterial species, including Escherichia coli , Citrobacter braakii , C. freundii , Klebsiella pneumoniae , Hafnia alvei , Enterobacter kobei , S. aureus , S. epidermidis , S. saprophyticus , S. simulans , S. warneri , S. xylosus , and M. sciuri . Among Staphylococcaceae isolates, 17.6% were resistant to oxacillin and 23.5% to gentamicin. Regarding the Enterobacteriaceae isolates, 41.2% were resistant to streptomycin. Ten isolates (two E. coli , one S . epidermidis , two S. saprophyticus , one S. simulans , one S . warneri and three M. sciuri ) were considered multidrug-resistant (MDR). Notably, none of the targeted genes ( mecA , sea , see , sec , stx1 , stx2 , eae ) were detected by PCR. These findings suggest that flies can disseminate important resistant opportunistic bacteria in meat processing environments, posing concerns due to the capacity of flies to transmit these bacteria across food, processing facilities, animals and humans. These results underscore the need for continuous AMR surveillance and effective vector control to reduce the risks posed by flies in meat processing environments.

Er and Er/Yb doped TiO2 solar-light-active photocatalysts for minocycline removal from water and wastewaters: Effect of synthesis and immobilization into MICROSCAFS® - Sofia Moreira Fernandes; Beatriz Trindade Barrocas; Ana Maria Ferraria; Luís F. Santos; M. Conceição Oliveira; Markus Niederberger; Ana C. Marques (Chemosphere, 2026)

Pyridin-3-carbohydrazide strongly impairs Mayaro and Chikungunya virus replication in vitro - Nancy Araceli Juárez Contreras; Natasha Marques Cassani; Mikaela dos Santos Marinho; Giulia Magalhães Ferreira; Maria Eduarda Trevisan Aguillar da Silva; João Victor Rodrigues Dutra; Juliana Roberta Torini; Sainan Wang; Kelyssa Vitória Rodrigues Dantas; Isabela Dolci; Mariana Ortiz de Godoy; Lavinia Cipriano; et al. (Archives of Virology, 2026)
Alphaviruses, including Mayaro virus (MAYV) and Chikungunya virus (CHIKV), pose a growing public health threat, with increasing reports worldwide and no licensed antiviral treatments available. This study evaluated the antiviral activity of pyridine-3-carbohydrazide (P-3-C) against MAYV (strains BeAr and TRVL) and CHIKV (strain La Reunion, LR). Vero E6 or U-2OS cells were infected and treated with P-3-C for 24 h, and cell viability and replication levels were assessed. The 50% cytotoxic concentration (CC 50 ), 50% effective concentration (EC 50 ), and selective index (SI) were calculated. P-3-C showed concentration-dependent activity, strongly inhibiting post-entry stages of MAYV BeAr replication. Treatment reduced intracellular viral RNA levels by 2 log 10 compared with controls and effectively decreased viral RNA release. P-3-C also inhibited MAYV TRVL (SI > 29.4) and CHIKV LR (SI > 48.8) in Vero E6 cells and retained selectivity in U-2OS cells (SI = 3.9 and 6.4, respectively). In a CHIKV U-2OS subgenomic replicon, an SI of 4.1 was found. Additionally, Fluorometric FRET-Based and MicroScale Thermophoresis (MST) assays indicated that P-3-C inhibited the nsP2 protease activity (IC 50 = 12 µM ± 2) and exhibited binding affinity for nsP4 polymerase ( K d = 54 µM ± 1) from CHIKV, thereby suggesting that these non-structural proteins are potential molecular targets. Molecular docking positioned P-3-C within the catalytic pockets of nsP2 and nsP4 of both viruses. Overall, the data suggest that P-3-C exhibits a potential multitarget mechanism of action and highlight its antiviral activity against different alphavirus strains; however, this efficacy could be dependent on the cell line used.

Palynotaxonomy of endemic species of Anteremanthus H. Rob., Hololepis DC., Maschalostachys Loeuille and Roque, and Proteopsis Mart. and Zucc. ex Sch.Bip. (Asteraceae: Vernonieae: Lychnophorinae) from Brazil - Lorena Nunes Lourenço Queiroz; Mateus Henrique Lauriano; Ana Junia Fernandes; Filipe Monte-Negro dos Santos Jacobi; Marco Thullio Arantes Santos; Luciana Maria Ramos Santos; Vania Gonçalves-Esteves; Danilo Marques (Palynology, 2026)

Prognostic factors in cats with squamous cell carcinoma treated with electrochemotherapy - André Gustavo Alves Holanda; Carlos Eduardo Fonseca-Alves; Aline Magalhães Ambrósio; Lilian Rose Marques de Sá; Marcelo Monte Mor Rangel; Genilson Fernandes de Queiroz; Julia Maria Matera (The Veterinary Journal, 2026)

Assessing coral nursery performance on reefs in Northeast Brazil under bleaching and anthropogenic pressures - Karina Massei; Maria Cecilia Silva Souza; Larissa Fernandes de Lavor; Carlos Alberto Cavalcanti Soares; Márcia Elisabeth Dementshuk; Amanda de Souza Vasconcelos; Patrícia de Moura Almeida; George Emmanuel Cavalcanti de Miranda; Pablo Riul; Frederico Gustavo Rodrigues França; Pedro Costa Guedes Vianna; Celso Augusto Guimarães Santos; et al. (Marine Pollution Bulletin, 2026)

Corrigendum to “Co-occurrence of microplastics and endocrine-disrupting chemicals in subantarctic seabirds” [J. Hazd. Mater. 509 (2026) 142018] - Joana Fragão; Clara Manno; Richard A. Phillips; Sara C. Cunha; José O. Fernandes; Luís A.E. Batista de Carvalho; Maria Paula M. Marques; José C. Xavier; Filipa Bessa (Journal of Hazardous Materials, 2026)

Unravelling the role of organic ligands in Zn(II) diffusion and sorption mechanisms in compacted Na-illite - Xiaoyan Wei; Bin Ma; Martin A. Glaus; Luc R. Van Loon; Duoqiang Pan; Maria Marques Fernandes; Rainer Dähn; Wangsuo Wu; Sergey V. Churakov (Geochimica et Cosmochimica Acta, 2026)

Pyriproxyfen and diflubenzuron pesticides impair human adipose stem cell function: evidence of redox imbalance, KDM6B upregulation, and dysregulated adipogenesis - Ana Beatriz Marques Abel; Andressa França Sousa Bispo; Jussara de Jesus Simao; Artur Francisco da Silva Neto; Julia Fernandes Barcella; Lila Missae Oyama; Bruno Fiorelini Pereira; Allain Amador Bueno; Maria Isabel Cardoso Alonso-Vale (Food and Chemical Toxicology, 2026)

Correction: Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)

Influence of raw material on the physical-chemical profile of cachaça: effects of variety and sugarcane cutting conditions - Maria Augusta L. S. M. Marques; Maria G. Cardoso; Wilder D. Santiago; Guilherme V. Pimentel; Tharyn Reichel; Antonia Isadora Fernandes; Sara C. S. Silva; Maria Luisa Teixeira; Danubia Ap. C. S. Rezende; David L. Nelson (Food Additives & Contaminants: Part A, 2026)

Influence of coral reef morphology on wave climate and sea-level rise projections along a reef-protected beach in Northeast Brazil - Larissa Fernandes de Lavor; Maria Cecilia Silva Souza; Karina Massei; Alexandre dos Santos Souza; Valdir do Amaral Vaz Manso; Virgínio Henrique de Miranda Lopes Neumann; Pedro Costa Guedes Vianna; Christianne Maria da Silva Moura; Nadja Cecília de Freitas Silva; Richarde Marques da Silva; Rogério dos Santos Ferreira; Jefferson da Costa Silva; et al. (Regional Studies in Marine Science, 2026)

Co-occurrence of microplastics and endocrine-disrupting chemicals in subantarctic seabirds - Joana Fragão; Clara Manno; Richard A. Phillips; Sara C. Cunha; José O. Fernandes; Luís A.E. Batista de Carvalho; Maria Paula M. Marques; José C. Xavier; Filipa Bessa (Journal of Hazardous Materials, 2026)

Phytotoxicity and metal mobility in soils contaminated with mine tailings - Andressa Cristhy Buch; Maria Elizabeth Fernandes Correia; Júlia Carina Niemeyer; Douglas Brian Sims; Eduardo Duarte Marques; Krishna Kumar Yadav; Ahmad J. Obaidullah; Camila Rodrigues e Silva; Emmanoel Vieira da Silva-Filho (Environmental Geochemistry and Health, 2026)
The consumption of vegetables is essential for human health. However, in regions affected by mining activities, this practice may pose serious risks due to potential heavy metal contamination at the soil–plant interface. This study evaluated the phytotoxicity and metal mobility in lettuce cultivated in mine tailing-contaminated soils after the Córrego do Feijão dam failure (Brumadinho, Minas Gerais, Brazil). The increase in soil metal concentrations negatively influenced morphological parameters such as root and shoot length, fresh biomass, germination, chlorophyll content, and the pattern and frequency of stomata on the leaf surface. Translocation factors of Fe, Ni, Mn, Cd, Cu, Pb, and Zn from roots to shoots of lettuce indicated significant risks to human health. In shoots, the concentrations of As, Cd, Pb, and Cu exceeded the maximum permissible limits for human consumption in lettuce and other leafy Asteraceae by up to 407-, 98-, 5,483-, and 28-fold, respectively. These results highlight the urgent need for mitigation, remediation, and protective strategies to safeguard human and animal health in mining regions, particularly where mining, agriculture, and livestock production coexist.

Agricultural use of water and nutrients from the saline industry effluent in the semi-arid region of potiguar: interrelationships of soil attributes and physiological indices of forage sorghum - Diego José da Costa Bandeira; Jeane Cruz Portela; Rafael Oliveira Batista; Blake Charles Diniz Marques; Joaquim Emanuel Fernandes Gondim; Jussiara Sonally Jácome Cavalcante; Maria Clara Correia Dias; Antônio Gustavo de Luna Souto; José Francismar de Medeiros; Rodrigo Rafael da Silva; Paulo Jardel Mota; Geisiane Xavier de Matos; et al. (Water, Air, & Soil Pollution, 2026)

Antiarthritic property and toxicological evaluation of the tea prepared from Ximenia americana barks - Gabriela Fernandes Oliveira Marques; Francisco Glerison da Silva Nascimento; Mário Rogério Lima Mota; Ana Paula Negreiros Nunes Alves; Paulo Goberlânio Barros Silva; Maria Gonçalves Pereira; Rondinelle Ribeiro Castro; Ana Maria Sampaio Assreuy (Advances in Traditional Medicine, 2026)
Ximenia americana L. (Olacaceae), popularly known as wild plum, northern plum or Brazilian plum, is used in the folk medicine to treat several inflammatory conditions. This study evaluated the effect of the tea, containing total carbohydrates (44.8%), polyphenols (28 gallic acid equivalent - GAE) and proteins (1.3%), and the polysaccharide fraction (FII) of X. americana barks (Tea-Xa) on rat zymosan-induced arthritis, along with the acute toxicity of Tea-Xa given per oral . Female rats ( N = 36; 200–220 g) received Tea-Xa (30–300 mg/kg; p. o. ) or FII (1 mg/kg; i.v.) 2 h after zymosan-induced arthritis, being evaluated for hypernociception, edema and articular leukocyte influx, histopathological alterations (inflammatory signs, tissue necrosis and disorganization, edema). For toxicity (OECD-423) female rats ( N = 9; 170–200 g) received per oral Tea-Xa (300 or 2000 mg/kg) and were observed for behavioral (14 days) and hematological, biochemical and histopathological parameters (day 14). Tea-Xa and FII reduced joint hypernociception and edema (47%), articular cavity neutrophils (83%) and nitrite (55%). Joint histopathological analysis revealed that Tea-Xa (30–300 mg/kg) and FII reduce tissue disorganization, and Tea-Xa attenuates the inflammatory infiltrate, necrosis and tissue disorganization. Tea-Xa (LD50 greater than 2000 mg/kg/body weight) did not alter body weight, relative organ mass, liver and kidney function markers, or tissue structure. No alterations were observed of most animal behavioral parameters. The polysaccharides of X. americana possess anti-inflammatory and antinociceptive effects on zymosan-induced arthritis and Tea-Xa did not produce adverse effects or mortality.

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Genetic parameters for litter and carcass traits in Landrace and Yorkshire pigs - Iasmin Marques Rocha; Giovanna Maria dos Santos Câmara; Maria Victória Henrique Genuíno; Ayrton Fernandes de Oliveira Bessa; Roney Teixeira; Luis Artur Loyola Chardulo; Rogério Abdallah Curi; Welder Angelo Baldassini; Guilherme Luis Pereira; Daniela do Amaral Grossi; Marcos Eli Buzanskas (Livestock Science, 2025)

Blockage of P2X7 receptor activation attenuated bone loss in ligature-induced model of periodontitis in rats - Nadine Linhares; Marco Aurelio Teófilo; Juliane Fernandes; Maria Jennifer Bernardino; Rachel Solidonio; Vanessa Sousa; Gisele Barreto; Everton da Silva; Ariana Maria Soares; Sthefane Feitosa; Denis Gonçalves; Delane Gondim; et al. (Purinergic Signalling, 2025)

ClaySor 2023: Implementation of the 2SPNE SC/CE sorption model and database for deep geological repository safety assessment - Olha Marinich; G. Dan Miron; Dmitrii A. Kulik; Maria Marques Fernandes; Bart Baeyens (Applied Geochemistry, 2025)

Physical Interactions between Cancer Cells and Tumor Microenvironment - Andressa Beatriz Apolinário da Silva Correia; Beatriz Medeiros de Souza Melo; Bruna Alves da Silva; Giovana Cruz Maciel; Guilherme Matheus Santos Marques Cavalcante; João Pedro Almeida dos Santos; Layza Maria Barbosa Silva; Luís Filipe Pereira Rocha; Maria Beatriz Cavalcante Brêda; Maria Eduarda Teixeira de Oliveira; Kayo Felipe Barbosa Lima; Luiz Ben-Hur de Oliveira Wanderley Nepomuceno; et al. (Cell Biochemistry and Biophysics, 2025)

Effects of mine tailings on the structure and diversity of microbial communities in riparian soils - Andressa Cristhy Buch; Krishna Kumar Yadav; Douglas B. Sims; Maria Elizabeth Fernandes Correia; Eduardo Duarte Marques; Ahmad J. Obaidullah; Emmanoel Vieira Silva-Filho (Environmental Geochemistry and Health, 2025)

Optimizing forest sector performance based on life cycle cost analysis and real options - Gustavo Alves de Melo; Thuliany Fernandes Araújo Paes; Jaqueline Severino da Costa; Carolina Souza Jarochinski e Silva; Luiz Gonzaga de Castro Júnior; Lucas Rezende Gomide; Maria Gabriela Mendonça Peixoto; Patrícia Guarnieri; Samuel Borges Barbosa; André Luiz Marques Serrano; Lucas Oliveira Gomes Ferreira (Science of The Total Environment, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Rice husk silica derived MICROSCAFS® for a green solar-driven photodegradation of minocycline in aqueous media - Francesca Langiano; Sofia Moreira Fernandes; Beatriz Trindade Barrocas; Anna Del Tedesco; Pietro Riello; Maria João Ferreira; Ana C. Marques; Massimo Sgarzi; Matteo Gigli; Claudia Crestini (Journal of Water Process Engineering, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Catalytic flash pyrolysis for recovery of gasoline-range hydrocarbons from electric cable residue using a low-cost natural catalyst: An analytical Py–GC/MS study - Vitor Fernandes Dias Lopes; José Luiz Francisco Alves; Edyjancleide Rodrigues da Silva; Júlio de Andrade Oliveira Marques; Dulce Maria de Araújo Melo; Marcus Antônio de Freitas Melo; Renata Martins Braga (Waste Management, 2024)

From port to port: the invasive bivalve Mytilopsis cf. sallei (Dreissenidae) is confirmed in southeastern Brazil - Maurício Romulo Fernandes; Cristiane Midori Suga; Maria Margarida Marques; Fabiano Salgueiro (Molluscan Research, 2024)

Influence of structural Fe content in clay minerals on selenite redox reactions: Kinetics and structural transformations - Yanting Qian; Andreas C. Scheinost; Sylvain Grangeon; Alwina Hoving; Sergey V. Churakov; Maria Marques Fernandes (Geochimica et Cosmochimica Acta, 2024)

Biometric analyses of drought tolerance in populations of Coffea canephora - Francisco Davi da Silva; Franciele Barros de Souza Sobreira; Edilson Marques; Cássio Fernandes Torres; Paulo Sérgio Volpi; Paulo Cezar Cavatte; Maria Amélia Gava Ferrão; Taís Cristina Bastos Soares (Euphytica, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

High-resolution mapping of soil carbon stocks in the western Amazon - Cássio Marques Moquedace; Clara Glória Oliveira Baldi; Rafael Gomes Siqueira; Irene Maria Cardoso; Emanuel Fernando Maia de Souza; Renildes Lúcio Ferreira Fontes; Márcio Rocha Francelino; Lucas Carvalho Gomes; Elpídio Inácio Fernandes-Filho (Geoderma Regional, 2024)

Snake and arthropod venoms: Search for inflammatory activity in human cells involved in joint diseases - Miryam Paola Alvarez-Flores; Isabel de Fatima Correia Batista; Isadora Maria Villas Boas; Michelle Cristiane Bufalo; Jean Gabriel de Souza; Douglas Souza Oliveira; Giuliano Bonfá; Cristina Maria Fernandes; Rafael Marques Porto; Flavio Lichtenstein; Gisele Picolo; Denise V. Tambourgi; et al. (Toxicon, 2024)

Cation-exchange properties of the Mesozoic sedimentary sequence of Northern Switzerland and modelling of the Opalinus Clay porewater - Maria Marques Fernandes; Martin Mazurek; Paul Wersin; Raphael Wüst; Bart Baeyens (Applied Geochemistry, 2024)

Tobacco exposure, but not aging, shifts the frequency of peripheral blood B cell subpopulations - Thalyta Nery Carvalho Pinto; Cibele Cristine Berto Marques da Silva; Regina Maria Carvalho Pinto; Alberto José da Silva Duarte; Gil Benard; Juliana Ruiz Fernandes (GeroScience, 2023)

Adsorption of Ba and 226Ra on illite: A comparative experimental and modelling study - Maria Marques Fernandes; Martina Klinkenberg; Bart Baeyens; Dirk Bosbach; Felix Brandt (Applied Geochemistry, 2023)

Prevention, protocols, and lab capacity: lessons from a norovirus outbreak in the Algarve - Regina Sá; Joana Roque; Pedro Marques Mendes; Inês Gonçalves; Judite Sousa; Cátia Matos; Álvaro Júnior; Anabela Coelho; Cristina Belo Correia; Vera Manageiro; Corrado Minetti; Rita de Sousa; et al. (Archives of Virology, 2023)

Geographical influences on the chemical composition and antifungal activity of Xylopia aromatica (Lam.) Mart. leaf essential oil - Maria Aparecida Ribeiro Vieira; Letícia Galhardo Jorge; Camila Marçon; Felipe Girotto Campos; Andrew Matheus Frederico Rozada; Gisele de Freitas Gauze; Flávio Augusto Vicente Seixas; Márcia Ortiz Mayo Marques; Rinaldo Poncio Mendes; Carmen Silvia Fernandes Boaro (South African Journal of Botany, 2023)

Multi-proxy assessment of coral reef formation and biotic-abiotic diversity in an urban coastal reef ecosystem in northeastern Brazil - Karina Massei; Maria Cecília Silva Souza; Richarde Marques da Silva; Virgínio Henrique de Miranda Lopes Neumann; Valdir do Amaral Vaz Manso; Pedro Costa Guedes Vianna; Antonio Vicente Ferreira Junior; Christianne Maria da Silva Moura; Larissa Fernandes de Lavôr; Rafael de Carvalho Araújo; Celso Augusto Guimarães Santos (Science of The Total Environment, 2023)

Large-scale grid-based detection in occupancy surveys of a threatened small mammal: A comparison of two non-invasive methods - Alexandra Oliveira; Denis Medinas; João Craveiro; Catarina Milhinhas; Helena Sabino-Marques; Tiago Mendes; Giulia Spadoni; André Oliveira; Luís Guilherme Sousa; Joaquim T. Tapisso; Sara Santos; Margarida Lopes-Fernandes; et al. (Journal for Nature Conservation, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Chironomus sancticaroli (Diptera: Chironomidae) in ecotoxicology: laboratory cultures and tests - Emília Marques Brovini; Haroldo Lobo; Raquel Fernandes Mendonça; Clarice Maria R. Botta; Ana Luiza Rangel Linhares Lima; Beatriz Corrêa Thomé de Deus; Simone Jaqueline Cardoso (Ecotoxicology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Temporal analysis of environmental quality of Ponta Negra beach (Natal-RN) related to coastal erosion: what has changed in 10 years? - Janiele Andrade Borges; Josicleide de Moura Pereira; Luana Silvestre Fernandes; Zaira Marques de Souza; Maria Christina Barbosa de Araújo; Jacqueline Santos Silva-Cavalcanti (Environmental Monitoring and Assessment, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Voxel-Based Morphometry and Relaxometry Demonstrate Macro- and Microstructural Damages in Spinocerebellar Ataxia Type 3 - Lívia Leite Góes Gitaí; Manoel Alves Sobreira-Neto; Paula Rejane Beserra Diniz; Alan Luiz Éckeli; Regina Maria França Fernandes; Wilson Marques; Antonio Carlos Santos (The Cerebellum, 2022)

New record of the bat falcon (Falco rufigularis) in northeastern Brazil: Implications for its future distribution under climate change - Maria Eduarda Alves Ferreira; Rodrigo Ferraz Jardim Marques; Hélio Francisco Leite; Alexandre M. Fernandes (Biologia, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Detecting the attack of the fall armyworm (Spodoptera frugiperda) in cotton plants with machine learning and spectral measurements - Ana Paula Marques Ramos; Felipe David Georges Gomes; Mayara Maezano Faita Pinheiro; Danielle Elis Garcia Furuya; Wesley Nunes Gonçalvez; José Marcato Junior; Mirian Fernandes Furtado Michereff; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl Alberto Alaumann; Veraldo Liesenberg; Lúcio André de Castro Jorge; et al. (Precision Agriculture, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Effect of Nitrogen Sources on Photosynthesis and Biosynthesis of Alkaloids and Leaf Volatile Compounds in Annona sylvatica A. St.-Hil - Patricia Luciana Carriel Corrêa; Iván De-la-Cruz-Chacón; Marília Caixeta Sousa; Maria Aparecida Ribeiro Vieira; Felipe Girotto Campos; Marcia Ortiz Mayo Marques; Carmen Sílvia Fernandes Boaro; Gisela Ferreira (Journal of Soil Science and Plant Nutrition, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Glyphosate: A Review on the Current Environmental Impacts from a Brazilian Perspective - Jonathas Gomes de Carvalho Marques; Klayde Janny da Silva Veríssimo; Bruna Soares Fernandes; Silvio Romero de Melo Ferreira; Suzana Maria Gico Lima Montenegro; Fabrício Motteran (Bulletin of Environmental Contamination and Toxicology, 2021)

The auxin-producing Bacillus thuringiensis RZ2MS9 promotes the growth and modifies the root architecture of tomato (Solanum lycopersicum cv. Micro-Tom) - Bruna Durante Batista; Manuella Nóbrega Dourado; Everthon Fernandes Figueredo; Renata Ockner Hortencio; João Paulo Rodrigues Marques; Fernando Angelo Piotto; Maria Letícia Bonatelli; Matthew L. Settles; João Lucio Azevedo; Maria Carolina Quecine (Archives of Microbiology, 2021)

Embryonic development of Kinosternon scorpioides (Testudines: Kinosternidae) - Brenda Stefany dos Santos Braga; Dário Lisboa Fernandes-Neto; Relionan Pimentel Leal; Samantha Ribeiro Silva; Maria Auxiliadora Pantoja Ferreira; Verônica Regina Oliveira-Bahia; José Ribamar Felipe Marques; Diva Anelie de Araújo Guimarães (Zoomorphology, 2021)

Which Factors in Spinocerebellar Ataxia Type 3 Patients Are Associated with Restless Legs Syndrome/Willis-Ekbom Disease? - Lívia Leite Góes Gitaí; Alan Luiz Éckeli; Manoel Alves Sobreira-Neto; Paula Rejane Beserra Diniz; Antônio Carlos Santos; Wilson Marques Júnior; Regina Maria França Fernandes (The Cerebellum, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Amino-Fe3O4-functionalized multi-layered graphene oxide as an ecofriendly and highly effective nanoscavenger of the reactive drimaren red - Tiago José Marques Fraga; Luiz Filipe Félix da Silva; Letticia Emely Maria de Lima Ferreira; Maryne Patrícia da Silva; Daysianne Mikaella dos Santos Marques Fraga; Caroline Maria Bezerra de Araújo; Marilda Nascimento Carvalho; Jorge Vinicius Fernandes de Lima Cavalcanti; Marcos Gomes Ghislandi; Maurício Alves da Motta Sobrinho (Environmental Science and Pollution Research, 2020)

Toxicological evaluation of nail polish waste discarded in the environment - Israel Felzenszwalb; Andreia da Silva Fernandes; Lara Barroso Brito; Gisele Augusto Rodrigues Oliveira; Paula Aquino Soeiro Silva; Maria Elena Arcanjo; Monica Regina da Costa Marques; Taynah Vicari; Daniela Morais Leme; Marta Margarete Cestari; Elisa Raquel Anastacio Ferraz (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Whole genome sequencing of a ST2594 MRSA strain causing non-mucosal preoperative colonization and low-grade postoperative infection - Leonardo Ribeiro Bastos; Maria Clara Fernandes Martins; Rodolpho Mattos Albano; Elizabeth Andrade Marques; Robson Souza Leão (Antonie van Leeuwenhoek, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Intralesional uridine-5′-triphosphate (UTP) treatment induced resistance to Leishmania amazonensis infection by boosting Th1 immune responses and reactive oxygen species production - Camila Marques-da-Silva; Mariana M. Chaves; Maria Luiza Thorstenberg; Vanessa R. Figliuolo; Flávia S. Vieira; Suzana P. Chaves; José Roberto Meyer-Fernandes; Bartira Rossi-Bergmann; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva (Purinergic Signalling, 2018)

Successful Treatment of Canine Sporotrichosis with Terbinafine: Case Reports and Literature Review - Paula Gonçalves Viana; Anna Barreto Fernandes Figueiredo; Isabella Dib Ferreira Gremião; Luisa Helena Monteiro de Miranda; Isabela Maria da Silva Antonio; Jéssica Sepulveda Boechat; Ana Caroline de Sá Machado; Manoel Marques Evangelista de Oliveira; Sandro Antonio Pereira (Mycopathologia, 2018)

The semi-synthetic molecule [4″,5″] dihydro-obovatin isolated from Tephrosia Toxicaria pers reduces zymosan-induced temporomandibular joint inflammatory hypernociception in rats - Danielle Rocha do Val; Hellíada Vasconcelos Chaves; Francisco Isaac Fernandes Gomes; Rodrigo da Silva Santos; Antonio Mateus Gomes Pereira; Igor Iuco Castro da Silva; Vicente de Paulo Teixeira Pinto; Lissiana Magna Vasconcelos Aguiar; Norma Maria Barros Benevides; Francisca Renata Lopes da Silva; Jair Mafezoli; Jackson Nunes e Vasconcelos; et al. (Medicinal Chemistry Research, 2018)

Standardization and Prevalence of the Booster Phenomenon: Evaluation Using a Two-Step Skin Test with 43 kDa Glycoprotein in Individuals from an Endemic Region of Paracoccidioidomycosis - Ana Paula C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Rinaldo P. Mendes; Anamaria M. M. Paniago (Mycopathologia, 2017)

Azospirillum spp. from native forage grasses in Brazilian Pantanal floodplain: biodiversity and plant growth promotion potential - Mayara S. T. Souza; Valter A. de Baura; Sandra A. Santos; Paulo Ivan Fernandes-Júnior; Fábio B. Reis Junior; Maria Rita Marques; Gecele Matos Paggi; Marivaine da Silva Brasil (World Journal of Microbiology and Biotechnology, 2017)

Dual effects of a lectin from the green seaweed Caulerpa cupressoides var. lycopodium on inflammatory mediators in classical models of inflammation - Ismael Nilo Lino de Queiroz; Ana Luíza Gomes Quinderé; José Ariévilo Gurgel Rodrigues; Edfranck de Sousa Oliveira Vanderlei; Natássia Albuquerque Ribeiro; Renata Line da Conceição Rivanor; Kátia Alves Ribeiro; Chistiane Oliveira Coura; Karuza Maria Alves Pereira; Hellíada Vasconcelos Chaves; Mirna Marques Bezerra; Ianna Wivianne Fernandes de Araújo; et al. (Inflammation Research, 2015)

Adaptive plasticity of Laguncularia racemosa in response to different environmental conditions: integrating chemical and biological data by chemometrics - Iara da Souza; Marina Marques Bonomo; Mariana Morozesk; Lívia Dorsch Rocha; Ian Drumond Duarte; Larissa Maria Furlan; Hiulana Pereira Arrivabene; Magdalena Victoria Monferrán; Silvia Tamie Matsumoto; Camilla Rozindo Dias Milanez; Daniel Alberto Wunderlin; Marisa Narciso Fernandes (Ecotoxicology, 2014)

Evaluation of Paracoccidioides brasiliensis Infection by gp 43 Intradermal Test in Rural Settlements in Central-West Brazil - Ana Paula da C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Anamaria M. M. Paniago (Mycopathologia, 2013)

The involvement of the HO-1 pathway in the anti-inflammatory action of a sulfated polysaccharide isolated from the red seaweed Gracilaria birdiae - Edfranck de Sousa Oliveira Vanderlei; Ianna Wivianne Fernandes de Araújo; Ana Luíza Gomes Quinderé; Bruno Pedrosa Fontes; Ygor Raphael Gomes Eloy; José Ariévilo Gurgel Rodrigues; Antonio Alfredo Rodrigues e Silva; Hellíada Vasconcelos Chaves; Roberta Jeane Bezerra Jorge; Dalgimar Beserra de Menezes; Janaína Serra Azul Monteiro Evangelista; Mirna Marques Bezerra; et al. (Inflammation Research, 2011)

Redox-sensitive prosurvival and proapoptotic protein expression in the myocardial remodeling post-infarction in rats - Paulo Cavalheiro Schenkel; Angela Maria Vicente Tavares; Rafael Oliveira Fernandes; Gabriela Placoná Diniz; Mariane Bertagnolli; Alex Sander da Rosa Araujo; Maria Luiza Barreto-Chaves; Maria Flavia Marques Ribeiro; Nadine Clausell; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2010)

Groundwater Assessment at Santiago Island (Cabo Verde): A Multidisciplinary Approach to a Recurring Source of Water Supply - Paula Maria Carreira; José M. Marques; António Pina; António Mota Gomes; Paula A. Galego Fernandes; Fernando Monteiro Santos (Water Resources Management, 2010)

Sildenafil citrate concentrations not affecting oxidative phosphorylation depress H2O2 generation by rat heart mitochondria - Maria A. S. Fernandes; Ricardo J. F. Marques; Joaquim A. F. Vicente; Maria S. Santos; Pedro Monteiro; António J. M. Moreno; José B. A. Custódio (Molecular and Cellular Biochemistry, 2008)